Experimental Investigation of the LTC5553 Microcircuit in the Frequency Multiplication Mode - Y. Rumyantsev, K; N. Zikiy, A; N. Zlaman, P; O. Mamchenko, S (International Journal of Engineering and Technology, 2018)
Mixer chips have wide functionality, which is not always declared by the manufacturer. The purpose of the experimental study is to prove the possibility of implementing a frequency multiplier based on the mixer chip LTC5553. An experimental study of the LTC5553 chip in the mode of frequency multiplication was performed 2, 4 and 6 times. The second harmonic transmission coefficient is not less than minus 17.25 dB, for the fourth harmonic not less than minus 35 dB, for the sixth harmonic - not less than minus 42.67 dB. The transmission power factor depends little on the input power. Recommendations for modes of using a mixer as a frequency multiplier are given.Â